The Creation of the ‘People’ in Laclau’s Theory of Populism: a critical assessment - Ballacci, Giuseppe (2017)
Defining populism as a political articulation, rather than a specific ideology, Laclau has been one of the first scholars to show why the form and content of this phenomenon are strictly related. According to him, stylistic features such as vague, polarising and strong emotive discourse are not merely epiphenomenal elements of populism, which prove the irrationality of its ideology. They are constitutive elements of populism as they are necessary to create and maintain the division of society into two antagonistic blocs. Laclau’s theory of populism, however, has also been criticised for implicitly endorsing an authoritarian view of power. In this paper I argue that to better identify the source of the democratic deficit in such theory, we need to explore the combination of form and content it endorses. In order to do this I analyse Laclau’s account of the articulatory practices of populism, focusing on their rhetorical character in particular. My argument is that this account is democratically problematic, since being based on a merely formal understanding of rhetoric, inevitably reduces the rhetorical dimension of these practices to an instrumental and thus potentially manipulative logic. This logic presupposes and promotes a homogenised, passive, and unreflective idea of the ‘people’.